2007
DOI: 10.1002/fam.945
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous ignition in storage and production lines: Investigation on wood pellets and protein powders

Abstract: SUMMARYThree materials were tested in small-scale baskets of cubic dimensions and analyses were performed based upon the results according to the Frank-Kamenetskii (FK) method and the crossing point (CP) method.Comparison of the FK method and the CP method results was performed additionally. The activation energy E and the QA value were found. The relationship between critical ambient temperature and the storage size was determined as well as the relationship between CAT and time to maximum thermal runaway for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…After tested at different oven temperatures, reactor sizes, and pellet samples, the mean activation energy of 78.7 ±0.8 kJ/mol and a mean ∆ r hA of (4.2 ±2.5) × 10 6 kJ/(kg s) are obtained. The activation energy from this study is consistent with the reported values of 76–93 kJ/mol at 100–200 °C and 60–80 kJ/mol at 50–80 °C for the Swedish wood pellets.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…After tested at different oven temperatures, reactor sizes, and pellet samples, the mean activation energy of 78.7 ±0.8 kJ/mol and a mean ∆ r hA of (4.2 ±2.5) × 10 6 kJ/(kg s) are obtained. The activation energy from this study is consistent with the reported values of 76–93 kJ/mol at 100–200 °C and 60–80 kJ/mol at 50–80 °C for the Swedish wood pellets.…”
Section: Resultssupporting
confidence: 91%
“…With a limited oxygen supply, the cellulosic materials underwent pyrolysis that produced active char and a large amount of heat, instead of the gas oxidation combustion, commonly known as burning or flaming. It should be noted that the smoldering phenomenon can easily develop to a rapid flame spreading combustion once the air flow increases or other conditions change that might increase the oxidation rate . As we observed, the pellets started smoking after they were exposed to air for a couple of minutes and could easily develop to flame combustion.…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations